INFORMATION TECHNOLOGY THEOLOGY PARADIGM IN ISLAMIC EDUCATION MANAGEMENT - Rafdhi, Faiz; Masyitoh, Masyitoh; Fahrudin, Adi (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Theology is the study of divine philosophy related to His Essence and His attributes. Theology is also meaningful about the relationship of humans as creatures with their God as Khaliq. In this research, what is Information Technology Theology means the study of the philosophy of divinity in information technology and efforts to internalize Divine values in the application of Islamic education management through information technology. This research concludes that there is God in Information Technology, there is tajalli (manifestation) of God in information technology. This study agrees with Ibn Arabi's Huwa la Huwa concept, there is tajalli of his attributes such as al-Ahad, al-Shamad, laysa Kamitslihi Shay'un, The Organizing, The Justice, which can be internalized into the character of the manager of Islamic educational institutions as khalîfah fi al-ar?, through the application of information technology for Islamic educational institutions, so that there is a pious human being who is orderly, sincere, honest and fair according to the goals of Islamic education. It is also concluded that information technology is a way to internalize Divine values in Islamic educational institutions, better the application of information technology, better the quality of Islamic educational institutions. This research method is a qualitative research with a descriptive approach, which describes the meaning of information technology theology, application of information technology in Islamic educational institutions and the realization of Divine values through the application of information technology. The research method uses literature study, by classifying, comparing and relating concepts to the theories that are compiled.